Causal analysis and impact of a systematic error detected about consumption associated with trastuzumab - Nuria Bujaldón Querejeta; Dolores Camacho Romera; José Antonio Pomares Pastor; María Sánchez Garnes; Mauricio Martínez Ramírez; Mercedes González Delgado (Farmacia Hospitalaria)
Objective: determine the cause of the constant difference between the theoretical and real number of trastuzumab units consumed in an Intravenous Mixtures Unit. Methods: was studied the manual and electronic full procedure about preparing mixtures with trastuzumab. Was performed by visual observation and review of quantitative monitoring data from the electronic preparation support and safe system of the application Farmis-Oncofarm®. Results: difference between the optimum volume of trastuzumab contained in the summary of product characteristics and the same included in Farmis_Oncofarm® was found. Also found a defect of the optimum volume of 10ml syringes used in the reconstitution vials process. Conclusions: the default in the optimal volume of 10ml syringes used in the reconstitution process increases the real consumed units of trastuzumab. This produces a significant economic impact calculated in an annual additional cost in approximately 46.508 € without negative consequences for the patient